“How do we solve this task?": Parental scaffolding with full- and preterm toddlers - Erdmann, Kim; Vetter, Verena; Schäferling, Michaela; Reuner, Gitta; Hertel, Silke (Zeitschrift für Entwicklungspsychologie und pädagogische Psychologie, 2019)
Abstract. The study examines (a) whether gestational age relates to parental scaffolding (SCA), when controlling for child cognitive development, parenting stress, and socioeconomic status, and (b)...
Online veröffentlicht: 16. September 2020
Gesehen am 25.02.2026